Legal Hermeneutics in the Preparation of a Case in the Province of Bali - ., Astariyani; ., Sudiarta; W.P.D., Diah (Udayana Journal of Social Sciences and Humanities; Vol 3 No 1 (2019): UJoSSH, Feburary 2019DO - 10.24843/UJoSSH.2019.v03.i01.p06, 2019)
The purpose of this study intends to examine the legal politics of the formation of laws and regulations, especially regional law products that are focused on the formation of a case based on legal research methods and hermeneutic approaches. The formation of Perkada, which is based on hermeneutics in the form of interpretation, requires carefulness so as not to cause problems in the form of conflict norms or fuzzy norms. Based on these objectives a research question was proposed as a guide in examining the above issues, namely: 1) Basic application of legal hermeneutics; and2) Form of application in the formation of Perkada in Bali Province. The final result expected from this research is to obtain information, understanding, and study in the framework of the preparation of the laws and regulations, especially the drafting of regional law products, namely in the Province of Bali.